2024
DOI: 10.1037/dec0000223
|View full text |Cite
|
Sign up to set email alerts
|

Numeracy does not polarize climate change judgments: Numerate people are more knowledgeable and knowledge is power.

Jinhyo Cho,
Edward T. Cokely,
Madhuri Ramasubramanian
et al.

Abstract: Statistical numeracy skills have been found to be among the most robust general predictors of risk understanding and decision-making quality. However, some research suggests that when numerate people hold extreme worldviews they could use their skills to engage in motivated (biased) reasoning about controversial topics like climate change, further polarizing their judgments and beliefs. While suggestive, previous numeracy studies on this topic have neglected the highly influential role of knowledge in skilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 116 publications
0
1
0
Order By: Relevance
“…For example, one nationally representative survey of Americans in 2009 found that, for liberals, greater knowledge about climate change was associated with heightened support for climate mitigation policies, whereas the opposite association was found in conservatives [27]. The evidence base for scientific literacy leading to motivated reasoning about climate policy is mixed, however [26], including two nationally representative U.S. studies reporting null effects for motivated reasoning as a driver of climate policy polarization [28,29].…”
Section: Political Polarization Of Americans' Support For Climate Pol...mentioning
confidence: 99%
“…For example, one nationally representative survey of Americans in 2009 found that, for liberals, greater knowledge about climate change was associated with heightened support for climate mitigation policies, whereas the opposite association was found in conservatives [27]. The evidence base for scientific literacy leading to motivated reasoning about climate policy is mixed, however [26], including two nationally representative U.S. studies reporting null effects for motivated reasoning as a driver of climate policy polarization [28,29].…”
Section: Political Polarization Of Americans' Support For Climate Pol...mentioning
confidence: 99%